Copper and temperature modify microbial communities, ammonium and sulfate release in soil. Issue 6 (30th October 2015) - Ferreira, Rui; Gaspar, Helena; Gonzalez, Juan M.; Clara, Maria I.; Santana, Margarida M.
Abstract: Recent studies suggest an important role of thermophilic bacterial communities of the Phylum Firmicutes on soil C, N and S cycling, and a positive effect on crop productivity through the production of sulfate (SO$ _4^{2 - } $ ) and ammonium (NH$ _4^+ $ ), essential plant nutrients. Copper (Cu) is commonly supplemented to soils as a fungicide in phytosanitary treatments although its consequences to the bacterial communities is frequently overlooked. Herein, we report on the influence of temperature and Cu on the microbial communities, namely those of the Phylum Firmicutes, from a soil collected at an olive orchard in S Portugal. Community fingerprints and band identification through sequencing was combined with measurement of SO$ _4^{2 - } $ and NH$ _4^+ $ production at different supplemented amounts of Cu and at moderate and high temperatures (30°C and 50°C, respectively). Both temperature and Cu induced changes in these communities, selecting for specific bacteria. Temperature induced the dominance of Brevibacillus, and Cu addition to soil caused a reduction of SO$ _4^{2 - } $ release by soil bacteria. Ammonium production during bacterial growth at moderate and high temperatures was not affected by Cu addition. A Cu‐tolerant thermophilic isolate, belonging to the Bacillus genus, showed significant inhibition by high Cu concentrations and a reduction of NH$ _4^+ $ release during growth; genera Brevibacillus and Bacillus have been previously reported as high NH$ _4^+ $ and SO$ _4^{2 - } $ producers of the Firmicutes phylum. Results indicate that Cu treatments select specific tolerant bacterial strains which could influence natural soil fertilization in Cu‐treated orchards.